The Analysis of Test Instrument Needs for Indonesian Language Lesson - Firdha Khairunnisa; Mulyadi Eko Purnomo; Santi Oktarina (STAI Hubbulwathan Duri, 2022)
This research describes the learners' needs toward HOTS test instrument development for the seventh-grade learners of a Public Junior High School Palembang. Test instrument has important roles in finding out the learners' skills in understanding the materials. The stage of this research is part of research and development by Gall Borg. It is a stage of collecting data or information to determine the needs of a developed product. The findings showed the students’ needs for the HOTS-based developed instrument from the discussion of the questionnaire and interview. On the other hand, the teacher realized that HOTS-based questions and learning for students had not answered their needs. Therefore, the teacher had to revise. It could be done by adjusting the materials needed by learners with those considered relevant to HOTS.